Developments in Methods of Analysis for Naphthalene Sulfonates. (4th March 2017) - Hashemi, Sayyed Hossein; Kaykhaii, Massoud
ABSTRACT: Naphthalene sulfonates are highly water-soluble compounds, indicating a high mobility in aquatic systems along with high temperature stability, which are important substances in the chemical industry. This review covers analytical methods, instruments and techniques used for the pre-concentration and analysis of naphthalene sulfonates in different matrices. All analytical steps including the extraction from real samples, their detection by spectrophotometric and chromatographic techniques, as well as methods of identification of this class of compounds are described in detail. The methods normally employed for the extraction and pre-concentration of these compounds is solid-phase extraction (including molecularly imprinted polymers and anion-exchange), while their quantification are performed using high-performance liquid chromatography, capillary electrophoresis, gas chromatography–mass spectrometry, liquid chromatography–mass spectrometry and spectrophotometric techniques. In this review, in addition to chromatographic and spectrophotometric methods, electrochemical innovations appearing in the literature will be also explored.